DEVELOPMENT OF A LOW-COST BIODIGESTOR APPLIED IN FAMILY AGRICULTURE - Lopes, L. A.; Lourenzani, A. E. B. S.; dos Santos, C. V.; dos Santos, P. S. B. (Revista Brasileira de Engenharia de Biossistemas, 2020)
The residual biomass from Family Farming (animal waste, food scraps, waste from fruits and vegetables, whey, etc.) can be used for the production of biogas, which can be used as a heat source for space heating, cooking food, heating water and also as a source of electricity to activate small equipment for the activities carried out on the rural property. The installation of a biodigester allows energy self-sufficiency, electrification of machines used in production processes, reduction of contamination from water sources, less emission of greenhouse gases and reduced production cost resulting in a better quality of life, environmental benefits and economic viability of rural productive activities. However, the biodigesters available on the market are structures for medium or large biogas production, with a high cost of implantation for the small rural producer, thus making it impossible for him to have access to renewable energy production technology, given the above, the present project, aims to develop a low-cost biodigester using waste from family agriculture, which will enable microorganisms to perform the anaerobic biodigestion process, generating biogas and biofertilizer.